A re-examination of (the) same using data from spoken english A re-examination of (the) same using data from spoken english - Jean Wong (Ilha do Desterro, 2008)
This paper reports on a qualitative discourse analysis of 290 tokens of (the) same occurring in spoken American English. Our study of these naturally occurring tokens extends and elaborates on the analysis of this expression that
was proposed by Halliday and Hasan (l976). We also review other prior research on (the) same in our attempt to provide data-based answers to the following three questions: (1) under what conditions is the definite article the
obligatory or optional with same? (2) what are the head nouns that typically follow same and why is there sometimes no head noun? (3) what type(s) of cohesive relationships can (the) same signal in spoken English discourse? Finally,
we explore some typical pedagogical treatments of (the) same in current ESL/EFL textbooks and reference grammars. Then we make our own suggestions regarding how teachers of English as a second or foreign language might go
about presenting this useful expression to their learners. Este estudo apresenta uma análise qualitativa do discurso de 290 ocorrências de (the) same no Inglês Americano falado. Nosso estudo sobre essas ocorrências naturais amplia e elabora a análise desta expressão que foi proposta por
Halliday e Hassan (1976). Também revisamos investigações posteriores sobre (the) same com o intuito de fornecer respostas fundamentadas em um banco de dados para as três seguintes perguntas: (1) em quais condições o artigo
definido (the) é obrigatório ou opcional juntamente a same? (2) quais são os principais substantivos que tipicamente seguem same e por que, às vezes, não há substantivo? (3) que tipo(s) de relações coesivas pode (the) same indicar no
discurso do Inglês falado? Finalmente, exploramos alguns tratamentos pedagógicos típicos de (the) same nos atuais livros-texto e gramáticas de Inglês – L2/LE. Em seguida, sugerimos como os professores de Inglês, como
segunda língua ou língua estrangeira, poderiam ensinar essa útil expressão para seus alunos.